2010
DOI: 10.1523/jneurosci.1021-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaGlial Glutamate Transporter Eaat1 Is Regulated by Fringe-Mediated Notch Signaling and Is Essential for Larval Locomotion

Abstract: In the mammalian CNS, glial cells expressing excitatory amino acid transporters (EAATs) tightly regulate extracellular glutamate levels to control neurotransmission and protect neurons from excitotoxic damage. Dysregulated EAAT expression is associated with several CNS pathologies in humans, yet mechanisms of EAAT regulation and the importance of glutamate transport for CNS development and function in vivo remain incompletely understood. Drosophila is an advanced genetic model with only a single high-affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 73 publications
(94 reference statements)
3
89
1
1
Order By: Relevance
“…Instead, we propose they arise from Notch-dependent neuron-to-glial communication during embryogenesis. We previously found that Fringe sensitizes Notch to stimulation from developing axons bearing Delta, thus maintaining Prospero and Eaat1 expression in a subset of LG (Stacey et al, 2010;Thomas and van Meyel, 2007). Knowing now that Prospero + cells develop into astrocytes, these data support the idea that astrogenesis is promoted by neuron-to-glial Notch signaling.…”
Section: Astrocyte Generation From a Multipotent Glioblast Requires Psupporting
confidence: 65%
See 4 more Smart Citations
“…Instead, we propose they arise from Notch-dependent neuron-to-glial communication during embryogenesis. We previously found that Fringe sensitizes Notch to stimulation from developing axons bearing Delta, thus maintaining Prospero and Eaat1 expression in a subset of LG (Stacey et al, 2010;Thomas and van Meyel, 2007). Knowing now that Prospero + cells develop into astrocytes, these data support the idea that astrogenesis is promoted by neuron-to-glial Notch signaling.…”
Section: Astrocyte Generation From a Multipotent Glioblast Requires Psupporting
confidence: 65%
“…Also, mRNAs for Eaat1, the only Drosophila glutamate transporter (Besson et al, 2000), and Eaat2, a transporter for taurine and aspartate (Besson et al, 2005(Besson et al, , 2011(Besson et al, , 2000, were shown to be expressed in discrete subsets of glia in the embryonic CNS (Freeman et al, 2003; Soustelle et al, 2002;Stacey et al, 2010). We raised antisera to Eaat1 and Eaat2, and found that the Eaat1 antibody strongly labeled astrocytic membranes (Fig.…”
Section: Astrocytes and Ensheathing Glia Are Distinguished By Expressmentioning
confidence: 83%
See 3 more Smart Citations